PENGARUH MODEL PEMBERDAYAAN DAN DISIPLIN KERJA GURU TERHADAP KINERJA SEKOLAH DI SMA NEGERI 1 MENDO BARAT KABUPATEN BANGKA - Khairiyansyah Khairiyansyah; Bunga Sari (Holistic Journal of Management Research, 2015)
Empowerment model and work discipline is reladet to the school performance. This study aims to analyze and determine the effet of the empowerment model and work discipline of teachers on the school performance in SMA Negeri 1 Mendo Barat, Bangka Regency. Empowerment and work discipline of the teacher are able to increase the school performance. Theachers who were satisfied with the empowerment model that given by the principal and obey the school’s rule will give a good impact to the school performance. This study is quantitave descriptive survey approach. The amount of sample was 38 people. The study used cencus method. Independent variables consist of empowerment model (X1) and work discipline of the teachers (X2), while the dependent variable wash school performance (Y). Testing instrument used validity, reliability, and classical assumptions. While, the analysis data method using multiple linear regression with the F test and t-test. The result shows that the variables of empowerment model (X1) and work disicpiline of the teachers (X2) simultaneously has signifikan effect on the performance of schools in SMA Negeri 1 Mendo Barat Kabupaten Bangka. It is shown by the calculation of the F test that Fcount (33.251) > Ftable (3.23) with p value of 0.000 < 0.05. Moreover, the adjusted R Square value of 0.635, which means that the influence of independent variables on the dependent variable is 63.5%. Partially, the result of t test shows that variables of empowerment model (X1) and work discipline of the teachers (X2) has a significant effect on the dependent variable models (X1) with variable calculation empowerment (X1) tcount (2.693) > ttable (2.0301) and work disicipline of the teachers (X2) tcount (2.250) > ttable (2.0301)